The brave boy - Khan , Saniyasnain (Goodword Books: New Delhi, 2013)
The book narrates the story of Prophet Ibrahim (Abraham) and his son Ismail (Ishmael). It focuses on the moment when Prophet Ibrahim, in obedience to Allah's command, prepares to sacrifice his son. The story emphasizes themes of faith, obedience, and trust in Allah's plan. Through simple text and vibrant illustrations, the story captivates young minds, making complex concepts more relatable and understandable.